Aktivitas Kehidupan Manusia di Surga Telaah Qs. Yaasin Ayat 55-58 : (Studi Kitab Tafsir Ibnu Katsir) - Muhammad Yunus Lubis; H. Abdul Halim; Winda Sari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Every human being will inevitably face death, which marks not the end, but the beginning of an eternal life life in heaven. This study explores the concept of activities in heaven as described in QS. Yaasin verses 55–58, focusing primarily on Tafsir Ibn Kathir, and supported by other classical and modern interpretations. The research aims to uncover in detail what the inhabitants of heaven experience and engage in. Using a qualitative literature study approach, the research draws from tafsir books, journals, and other scholarly references to present a valid understanding. The findings reveal that the residents of heaven experience both spiritual and material pleasures. These include consuming delicious food and drinks that are not only abundant but tailored to their desires. Inhabitants also interact joyfully with others, including parents, children, and relatives provided those relatives were faithful and obedient to Allah during their earthly life. A central highlight of heavenly bliss is the divine gift from Allah SWT: the greeting and the vision of Allah SWT, which overwhelms them with such joy that they are oblivious to everything else. Ibn Kathir explains this vision as the peak of everlasting happiness, undisturbed by any worldly concern. This interpretation is enriched with insights from other scholars (mufassirun), providing a more complete picture of the nature of paradise. This study contributes to a deeper understanding of Qur'anic interpretation and serves as spiritual motivation for Muslims to strive for righteousness in this life, with the hope of experiencing the eternal joys described in the hereafter.